Design and analysis of sandwich structure for the application on FAR25 wing - Naik, Vivekanand K. (Cranfield University, 2021)
With the growing concern towards global warming and increase in fuel prices, many countries advocate stringent environmental laws to restrict any further damage to the environment. The new laws will affect how the future vehicles are designed. The aerospace industry is also one of the main contributors of pollution. To design better fuel-efficient aeroplanes, aero industry is switching to weight efficient materials. Since last few decades the aerospace industry is shifting from isotropic materials to composite materials to design weight efficient structures. The structures made up of composite materials are mostly in two different forms such as monolithic composite materials used on primary structures and composite sandwich materials which are commonly seen on the secondary structures. The research aims at investigating the sandwich structure as the potential material for the application on FAR25 type wing primary structure. The transport category airplanes with greater than 19 sets or the maximum take of weight (MTOW) is greater than 8618kg are referred to FAR25 type aeroplanes. In the first phase of the research, the focus is to assess the literature to find research gaps within the sandwich structures along with feedback from Airbus Research and Technology (R&T). In second phase, the focus is to investigate the stiffened panel design which is based on the current Airbus single aisle aeroplane. The review of sandwich structures and its current application on FAR25 structures along with the current research and development of sandwich material technology is conducted. The different failure modes of the sandwich structures are also investigated. In the third phase, parametric study and optimization of stiffened panel and sandwich panel is performed within the range of operational loads. In addition, the influence of core properties in improving the structural efficiency of sandwich structure is investigated. The research also focused on understanding the efficiency of different sandwich joints. In the final phase of the research the study looks into the design of hybrid/variable stiffness core to help tailoring core properties to improve the structural efficiency of sandwich panel. The research study demonstrated the importance of core properties in designing the efficient sandwich panel as potential material for the application on FAR25 primary structure. Investigation of novel variable core design has demonstrated how the tailoring of core properties can influence the overall performance of sandwich structure so that the core can be tailored as per different application. From the research it has shown that the sandwich core with single property structure can be still used on secondary structure whereas the tailored core design for the primary structure on FAR25 type aeroplanes. It is also shown that a better manufacturing process can add considerable value for sandwich materials.
Jamshidi, Jafar - Associate Supervisor
Keywords: stiffened panel design; sandwich material; sandwich joints; hybrid/variable stiffness core; structural efficiency; core properties